Sistem Informasi Monitoring Daerah Aliran Sungai Kota Semarang Berbasis Web - Azizah, Azizah; Jumi, Jumi; Mulyono, Tedjo (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
Processing river watersheds is very important because the risk of disasters caused by overflowing river water will be reduced if the watershed is well maintained. If DAS information is complete, DAS maintenance can run well. However, very little information is currently available. Therefore, we need a system that can be used to monitor DAS. The system will be a web-based Semarang City Watershed Monitoring Information System which can show the current condition of the watershed. This system has the ability to monitor watershed areas around Semarang, and if the watershed conditions are unstable, this system can repeat before any harm occurs to local residents. The results of watershed data collection can provide users with information regarding the location of dams and their descriptions, the river network in the watershed. Data collection is carried out by collecting information via the internet. Relevant data regarding watersheds which includes information on watershed conditions. The aim of this research is to build online-based monitoring media using content management systems such as WIX media so that it can expand monitoring of rivers that cannot be seen directly. Apart from that, it also aims to bring greater awareness to the current condition of River Watersheds (DAS). By designing appropriate monitoring media, we can more effectively introduce the actual situation of the watershed which has the potential to encourage increased awareness of environmental protection and management. The method used by this research is the Waterfall method in which there are several stages such as Requirements System, System and Software Design, Implementation and Until Testing, Integration System Testing, Operation and Maintenance. The results of this research indicate that the development of this website is to update existing information and make it easier for customers to access information about DAS anytime and anywhere.